2014
DOI: 10.1186/1477-7525-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and income-related social mobility in young adults

Abstract: BackgroundTo assess the association of income-related social mobility between the age of 13 and 30 years on health-related quality of life among young adults.MethodsIn 1988-89 n = 7,673 South Australian school children aged 13 years were sampled with n = 4,604 children (60.0%) and n = 4,476 parents (58.3%) returning questionnaires. In 2005-06 n = 632 baseline study participants responded (43.0% of those traced and living in Adelaide).ResultsMultivariate regressions adjusting for sex, tooth brushing and smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
3
10
1
Order By: Relevance
“…However, only individuals in the stable manual trajectory reported worse oral health by age 33 years than those in the stable nonmanual and the two upwardly mobile trajectories. The present findings reinforce the assumption that oral health in adult life may be more influenced by current rather than past socioeconomic experiences . Our findings also suggest that upward mobility, occurring either gradually (steady increase group) or in late adolescence (late steep increase group), may dilute the negative impact of living in manual social class early in life.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, only individuals in the stable manual trajectory reported worse oral health by age 33 years than those in the stable nonmanual and the two upwardly mobile trajectories. The present findings reinforce the assumption that oral health in adult life may be more influenced by current rather than past socioeconomic experiences . Our findings also suggest that upward mobility, occurring either gradually (steady increase group) or in late adolescence (late steep increase group), may dilute the negative impact of living in manual social class early in life.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that intergenerational mobility is related to adult oral health . In the Dunedin Study, upward mobility was associated with better dental but not periodontal status while downward mobility was associated with worse dental but not periodontal status .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, low socioeconomic conditions were not significantly associated with worse QoL, which differs from various investigative studies about the influence of these conditions on the levels of health of the population . This result may be justified, since the sample descriptively presented a homogeneous type of distribution, with regard to socioeconomic aspects, such as family income and the guardians’ educational level.…”
Section: Discussioncontrasting
confidence: 62%
“…The scientific literature presents a wide range of studies associating oral conditions with QoL in children, adolescents, adults and the elderly . Some also demonstrate the impact of social determinants on QoL . However, cross‐sectional studies in ID population which investigate the influence of both, clinical and nonclinical variables, on QoL are scarce .…”
Section: Introductionmentioning
confidence: 99%